Sanhuang Decoction Controls Tumor Microenvironment by Ameliorating Chronic Stress in Breast Cancer: A Report of Ninety Cases - Feng, Ming; Wang, Huanhuan; Zhu, Zhiyuan; Yao, Bowen; Li, Yongfei; Xue, Jingxian; Cao, Sihan; Shao, Xinyi; Xu, Yanlei; Sohn, Ki Cheul; Shin, Im Hee; Yao, Chang (Frontiers in Oncology, 2021)
Long-term endocrine treatment which results in estrogen deprivation causes chronic stress associated with a series of uncomfortable symptoms leading not only to a decrease in quality of life but also to cancer recurrence, which may be mediated primarily through the enhanced expression of angiogenic factors, as well as a series of inflammatory microenvironmental changes that favor tumor progression. In this study, we designed a clinical trial and aimed to explore the effects of Sanhuang Decoction (SHD) treatment on chronic stress, inflammatory factors, and breast cancer recovery. A total of 90 patients with breast cancer who met the inclusion/exclusion criteria were randomly allocated to a treatment or control group. The treatment group received the standard endocrine treatment and the traditional Chinese medicine decoction known as SHD. The control group received the standard endocrine treatment only. The treatment period was 6 months. The modified Kupperman Menopausal Index, the self-rating anxiety scale, and the self-rating depression scale were evaluated once per month. The body microenvironment plasma indices related to chronic stress, such as oxidative and antioxidative stress markers, inflammatory factors, hemorheology, coagulation, lipid and D-dimer, immunologic functions, tumor biomarkers, and angiogenic factors of the vascular endothelial growth factor (VEGF) were measured before and after 6 months of treatment. After treatment for 5 months, the scores in the treatment group decreased to nearly normal levels and the control group showed no significant improvement. After treatment for 6 months, all indices related to the body microenvironment, as well as the tumor biomarkers and carcinoembryonic antigen, carbohydrate antigen 153, and angiogenic factor VEGF levels improved significantly to normal levels in the treatment group. Our primary research showed that treatment with SHD effectively improved the quality of life of breast cancer patients by facilitating a change in the body microenvironment that controlled tumor growth and prevented drug resistance. Clinical Trial Registration Chinese Clinical Trial Registry, identifier ChiCTR-IIR-2000041413. Date of registration: 2017-06-07 (retrospective registration).